Pathological manifestations and damage map in historical heritage: a case study of the Basílica e Convento de Nossa Senhora do Carmo in Recife-PE (Research, Society and Development, 2022)
The city of Recife, capital of Pernambuco, is full of historic buildings that have pathological manifestations that reduce their useful life, degrade the structure and historical heritage. Currently, the study of conservation of buildings with historical interest has been gaining ground, generating discussions in several areas on the subject. The area of ​​engineering responsible for the study of pathological manifestations of buildings is essential in the preservation of historic buildings. The present research was developed with the purpose of making a survey of the pathological manifestations and the elaboration of the damage map of the Basilica e Convento de Nossa Senhora do Carmo. The criteria adopted for choosing the building were: listed by the Instituto do Patrimônio Histórico e Artístico Nacional (IPHAN), social importance, accessibility and availability of data. Through bibliographic research it was possible to analyze the history of the building and through inspections the pathological manifestations of its facades were identified and recorded. The most recurrent manifestations on the facade studied were dirt/black crust and detachment of paint. Visual inspection for the analysis of pathological manifestations is a fundamental tool for the treatment and preservation of historic buildings and the final product of the research helps in the execution of future maintenance, restoration and repairs.